Improvement of the 2007–2015 Earthquake Catalog Along the 300 km Long Postglacial Merasjärvi–Stuoragurra Fault Complex in Northern Fennoscandia Using Automatic Event Detection - Daniela Calle-Gardella; Claudia Pavez-Orrego; Diana Comte; Felix Halpaap; Odleiv Olesen; Alina Espinoza; Steven Roecker (Geosciences)
We present an updated and validated seismic catalog for the northern Fennoscandian region, focusing on postglacial faults from the Merasjärvi fault system in the southwest to the Iešjávri fault system in the northeast. This work involved a comprehensive review of continuous waveforms derived from open datasets from 2007 to 2015 and processed using the Regressive ESTimator algorithm. The primary objective was to refine the delineation of seismicity along the above-mentioned postglacial faults and highlight their seismic potential. Our analysis revealed distinct waveform patterns originating primarily from two main sources: approximately 15% were associated with areas mapped as postglacial faults, and the remainder of the events outside these areas, 89%, were concentrated in areas with active mines. Compared to previously reported events in the Fennoscandian Earthquake Catalogue (FENCAT), we observed a 22% increase in seismic activity within postglacial fault zones. These results demonstrate that the Regressive ESTimator algorithm not only improves the detection of tectonic seismicity but also effectively identifies seismic signals resulting from mining activities in the study area. The Merasjärvi, Lainio–Suijavaara, Palojärvi, and Maze and Iešjávri fault systems appear to form a continuous deformation complex of approximately 300 km long, which we propose naming the Merasjärvi–Stuoragurra fault complex.